Applications of simulation in maintenance research - Alabdulkarim, Abdullah A.; Ball, Peter D.; Tiwari, Ashutosh (World Academic Press, 2013)
The area of asset maintenance is becoming increasingly important as greater asset availability is demanded. This is evident in increasingly automated and more tightly integrated production systems as well as in service contracts where the provider is contracted to provide high levels of availability. Simulation techniques are able to model complex systems such as those involving maintenance and can be used to aid performance improvement. This paper examines engineering maintenance simulation research and applications in order to identify apparent research gaps. A systematic literature review was conducted in order to identify the gaps in maintenance systems simulation literature. The methodology applied identified peer- reviewed papers which were analysed for content and research direction. Simulation has been applied to model different maintenance sub-systems (asset utilisation, asset failure, scheduling, staffing, inventory, etc.) but these are typically addressed in isolation and overall maintenance system behaviour is poorly addressed, especially outside of the manufacturing systems discipline.
Keywords: Simulation, Maintenance; Discrete Event Simulation; Engineering Services